KOMPARATIF METODE PENSYARAHAN KITAB FATH AL-BÂRÎ DAN ‘UMDAH ALQÂRÎ SYARH SHAHIH AL-BUKHÂRÎ - Ja’far Assagaf (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
The article compares the interests of Islamic scholars(ulama‟) in the Hadith (book) of Shahih Bukhari. Two methods ofinterpreting hadith of Shahih Bukhari were taken from two differentbooks (kitab). They are Fath al-Bari which was written by Ibnu Hajar al-Asqalani and „Umdatul Qari which was written by Badr al-Dîn al-`Ainî.The explanation from Umdah al-Qârî is easier to understand than Fathal-Bari because it was arranged in systematic ways. On the other hand,Fath al-Bârî emphasizes on the explanation of the problems anddescribes the problems found in hadith of Shahih Bukhari in details.The differences among the Islamic scholars (ulama‟) in interpretinghadith of Shahih Bukhari show their interests in researching hadiths,which came originally from Prophet Muhammad PBUH.